UJI KETELITIAN CETAK PRODUK LENGKUNG PRINTER 3D ANET A8 - Yanuar Burhanuddin; Made Gita Arya Candra; Achmad Yahya Teguh Panuju; Suryadiwansa Harun (Machine : Jurnal Teknik Mesin, 2023)
This study aims to determine the accuracy of the Anet A8 3D Printer in printing curved products with the infill speed, print speed and layer height factors in order to obtain optimal results and determine the most influential parameters in printing curved products using the Anet A8 3D Printer. The method used in testing the accuracy of printing 3D printing products is Taguchi L9. From this study it can be concluded that the most optimal process parameters for the accuracy of the dimensions of the specimen diameter are successively for accuracy, namely layer height (0.3000 mm), infil speed (50 mm/s) and layer speed (30 mm/s) then the most optimal process parameters for the accuracy of the curved dimensions of the specimen are successively for accuracy, namely layer height (0.2000 mm), infil speed (50 mm/s). s) and layer speed (40 mm/s). The results of the ANOVA analysis show that the most contributed parameter in printing curved specimens with the diameter dimension is the layer height and the curved dimension is the infill speed.